Consumption in the Developed Society and the Need to Change the Business Philosophy of Marketing - Pechočiaková Svitačová, Eva (Studia Ecologiae et Bioethicae, 2025)
Consumption is a social activity, one of the objective prerequisites for better living conditions for people, and at the same time an important prerequisite for the functioning and development of a market economy. The study reveals that the efforts of many actors in the economy to make a profit are associated with the growth of consumption, with the development of a consumerist life strategy and a consumer culture. Consumption, on the one hand, allows individuals to liberate themselves, to express themselves, it is an expression of individualisation, but it is also a space for manipulation. In this context, attention has been drawn to certain forms of modern marketing which not only influence consumer demand or consumption, but also their lifestyles and identities. Alongside this, they promote consumerism, consumer culture and, in the long term, threaten sustainable development. In order to improve the quality of life of present and future generations the need to rethink some modern types of marketing and to change or reform the current marketing business philosophy is justified.